Double-crystal-phase nano-structure alloy hydrogen evolution catalyst as well as preparation method and application thereof
By forming a dual-crystal nanostructured alloy in a Ru-based catalyst, controlling the content of Mn and Ru and the formation of O-rich interfaces, the problem of reducing hydrogen productivity caused by the interaction between Ru and H atoms is solved, and an efficient electrocatalytic hydrogen evolution reaction is achieved.
Patent Information
- Application Number
- CN202510085834.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-20
AI Technical Summary
The strong interaction between Ru and H atoms in existing Ru-based catalysts hinders the desorption of H2, resulting in a decrease in hydrogen productivity.
By controlling the content of Mn and Ru elements, a two-crystalline nanostructure alloy is formed, including Mn-rich and Mn-leading phases, and a high-density O-rich interface is formed between the two phases as a catalytically active site.
The hydrogen adsorption and desorption process is optimized, the performance of electrocatalytic hydrogen evolution reaction is improved, and the productivity reduction problem caused by the interaction between Ru and H atoms in Ru-based catalysts is solved.
Smart Images

Figure CN119838596A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogen evolution electrocatalysts and heterogeneous phase structure alloy materials, and in particular to a twin-phase nanostructure alloy hydrogen evolution catalyst and a preparation method and application thereof. Background Art
[0002] The numerous pollution and development problems caused by the widespread burning of fossil fuels have attracted widespread attention. -1 , hydrogen has become an ideal solution to energy shortages and environmental pollution. Among the various hydrogen production methods, electrochemical water splitting, especially the electrocatalytic hydrogen evolution reaction, is considered to be an effective, sustainable and green synthesis strategy. The full name of the electrocatalytic hydrogen evolution reaction is Electrocatalytic Hydrogen Evolution reaction, abbreviated as HER. The precious metal platinum is recognized as the most advanced HER catalyst due to its optimal hydrogen binding ability; however, factors such as the low reserves and high price of platinum have greatly hindered its industrial application. Therefore, the current key challenge is to develop high-performance and low-cost hydrogen evolution electrocatalysts.
[0003] Ruthenium, as one of the precious metals, not only has an ideal price, about 5% of Pt, but also has excellent water dissociation ability, which is considered to be a theoretically suitable substitute for Pt. However, due to the strong interaction between Ru and H atoms, the application of Ru-based catalysts also faces limitations. According to the catalyst adsorption kinetics relationship, the strong interaction between Ru and H atoms will hinder the desorption of H2, resulting in a decrease in the productivity of hydrogen. Summary of the invention
[0004] In order to solve the problem that the strong interaction between Ru and H atoms in existing Ru-based catalysts hinders the desorption of H2, resulting in reduced hydrogen productivity, the purpose of the present invention is to provide a dual-phase nanostructured alloy hydrogen evolution catalyst and its preparation method and application.
[0005] To achieve the above objectives, the technical solution of the present invention is as follows.
[0006] The first aspect of the present invention provides a dual-phase nanostructured alloy hydrogen evolution catalyst, comprising a substrate and a dual-phase nanostructured alloy deposited on the surface of the substrate; the dual-phase nanostructured alloy is composed of the following elements in terms of atomic percentage:
[0007] Ru 56% to 62%, Mn 5% to 30%, Nb 8% to 30% and O 5% to 6%, totaling 100%; the dual-phase nanostructured alloy includes a Mn-rich phase and a Mn-poor phase, and an O-rich interface is formed between the Mn-rich phase and the Mn-poor phase, and the O-rich interface is a catalytic active site; the size of the Mn-rich phase is 1nm to 6nm.
[0008] The present invention mainly controls the content of Mn and Ru elements to obtain Mn-rich phases and Mn-poor phases of different sizes, and promotes the formation of an O-rich interface through the synergistic effect of the Mn-rich phase and the Mn-poor phase. The O-rich interface enhances the charge transfer and water dissociation kinetics, optimizes the hydrogen adsorption and desorption process, and thus improves the HER performance. In addition, the high-density O-rich interface provides abundant catalytic active sites, improves the HER catalytic performance, and solves the problem that the strong interaction between Ru and H atoms in the existing Ru-based catalysts will hinder the desorption of H2, resulting in a decrease in the productivity of hydrogen.
[0009] In the present invention, Ru can significantly affect the catalytic activity. Too high Ru elements will reduce the number of Mn-rich phases, thereby reducing the number of active interfaces formed in the Mn-rich phases. As an active element, Ru itself also plays an important role in improving the activity of the catalyst. Too low Ru will reduce the catalytic sites, thereby reducing the catalytic activity. Therefore, the Ru content should be controlled at 55% to 65%.
[0010] Through DFT calculation, it was found that in the O-rich interface, O atoms can reduce the energy barrier for the conversion of active hydrogen to H2. At the same time, O atoms can also improve the efficiency of the H2O dissociation step, resulting in RuMnNbO being superior to Pt-based catalysts in electrochemical H2 release. Among them, the lower the vacuum degree of the cavity, the lower the O content. The O content will affect the formation of the O-rich interface. Too low O content will lead to insufficient formation of the O-rich interface and reduce the active sites. However, too high O content will cause excessive oxidation of the metal elements, excessively reduce the adsorption energy of H at the active sites, and is not conducive to catalytic activity. Therefore, the O content should be controlled between 3% and 10%.
[0011] Preferably, the size of the Mn-rich phase is 1 nm to 2 nm, which helps to influence the size and number of the highly active O-rich interfaces, thereby improving the catalytic performance.
[0012] Preferably, the atomic percentage of the Mn element in the Mn-rich phase is 20% to 30%; and the atomic percentage of the Mn element in the Mn-poor phase is 10% to 15%.
[0013] In the present invention, the content of Mn element can affect the size of Mn-rich phase, and further affect the size and number of highly active O-rich interfaces. The formed high-density O-rich interfaces can provide abundant active sites, and further improve the catalytic performance.
[0014] Preferably, the Mn-rich phase is composed of the following elements in atomic percentage:
[0015] Ru 50% to 60%, Mn 20% to 30%, Nb 20% to 22% and O 3% to 8%, totaling 100%.
[0016] Preferably, the Mn-poor phase is composed of the following elements in terms of atomic percentage:
[0017] Ru 60% to 75%, Mn 10% to 15% and Nb 22% to 24%, totaling 100%.
[0018] The composition of the bicrystalline hydrogen evolution catalyst prepared in the present invention is the average composition of the bicrystalline hydrogen evolution catalyst, which is different from the composition of the Mn-rich phase and the composition of the Mn-poor phase; and the ratio of the Mn-rich phase to the Mn-poor phase will affect the total composition of the bicrystalline hydrogen evolution catalyst.
[0019] The second aspect of the present invention provides a method for preparing the dual-phase nanostructured alloy hydrogen evolution catalyst according to the first aspect, comprising the following steps:
[0020] The invention adopts magnetron sputtering technology and controls the contents of Mn and Ru elements to deposit a dual-phase nanostructured alloy containing a Mn-rich phase and a Mn-poor phase on the surface of a substrate, and forms an O-rich interface between the Mn-rich phase and the Mn-poor phase of the dual-phase nanostructured alloy; and adjusts the size of the Mn-rich phase to adjust the size and number of the O-rich interface, so as to provide catalytic active sites.
[0021] In the present invention, high-purity argon gas is used in the experiment. The oxygen that forms the O-rich interface mainly comes from the air in the vacuum chamber of the magnetron sputtering system. The residual air in the chamber is different under different vacuum degrees. Of course, it is not ruled out that it is oxygen in the pores in the target material. Therefore, there is a mixture of argon and air in the sputtering chamber under a certain vacuum degree.
[0022] Preferably, the process parameters for depositing the dual-phase nanostructured alloy are:
[0023] Ru, Mn, and Nb are used as targets; the background vacuum is 1×10 -5 Pa~5×10 -5Pa, the working gas pressure is 0.2Pa~0.4Pa, the distance between the substrate and the target is 15cm; the sputtering temperature is 20℃~30℃; taking Ru as the target, the sputtering power is 50watt~80watt; taking Mn as the target, the sputtering power is 50watt~80watt, and the sputtering voltage is 270V~430V; taking Nb as the target, the sputtering power is 50watt~80watt, and the sputtering voltage is 175V~280V; the deposition time is 45min~60min.
[0024] Preferably, before adopting the magnetron sputtering technology, the substrate is also pre-treated, and the pre-treatment is to perform acid immersion treatment on the cleaned substrate to improve the hydrophilicity of the substrate; the substrate is a carbon cloth substrate.
[0025] Preferably, argon is used as the working gas, and the mass flow rate of the sputtering argon gas is in the range of 30 sccm to 50 sccm.
[0026] The third aspect of the present invention provides an application of the dual-phase nanostructured alloy hydrogen evolution catalyst described in the second aspect in an electrocatalytic hydrogen evolution process.
[0027] Preferably, the specific application method comprises the following steps:
[0028] A twin-phase nanostructured alloy hydrogen evolution catalyst is deposited on the surface of a carbon cloth electrode to prepare a modified electrode; the modified electrode is used as a working electrode, a graphite rod is used as a counter electrode, and a saturated calomel electrode is used as a reference electrode to form a three-electrode system for electrocatalytic hydrogen evolution.
[0029] Beneficial effects of the present invention:
[0030] 1. The present invention mainly obtains Mn-rich phases of different sizes by controlling the composition of Mn and Ru elements, and promotes the formation of O-rich interfaces through the synergistic effect of Mn-rich / Mn-poor dual phases. The O-rich interface enhances the charge transfer and water dissociation kinetics, optimizes the hydrogen adsorption / desorption process, and thus improves the HER performance. In addition, the high-density O-rich interface provides abundant active sites, improves the catalytic performance, and solves the problem that the strong interaction between Ru and H atoms in the existing Ru-based catalysts will hinder the desorption of H2, resulting in reduced hydrogen productivity.
[0031] 2. In the present invention, the content of Mn element can affect the size of Mn-rich phase, and further affect the size of the formation of highly active O-rich interface. The formed high-density O-rich interface can provide abundant active sites, and further improve the catalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1It is a linear voltammetric scanning curve of a three-electrode system assembled with the dual-phase nanostructured alloy hydrogen evolution catalyst of Examples 1 to 3 as the working electrode.
[0033] Figure 2 It is a Tafel slope diagram of a three-electrode system assembled with the dual-phase nanostructured alloy hydrogen evolution catalyst of Examples 1 to 3 as the working electrode, wherein the abscissa is the logarithmic value of the current density and the ordinate is the potential.
[0034] Figure 3 The electrochemical impedance spectra of the three-electrode system assembled with the dual-phase nanostructured alloy hydrogen evolution catalysts of Examples 1 to 3 as working electrodes are shown in FIG. 1 , wherein Z′ represents the real part of the impedance; and −Z″ represents the inverse of the imaginary part of the impedance. Figure 3 The inset is an equivalent circuit diagram drawn based on EIS data. s is the solution resistance, R ct is the charge transfer resistor, and CPF 1 is a constant phase angle element.
[0035] Figure 4 The three-electrode system assembled with the dual-phase nanostructured alloy hydrogen evolution catalyst of Example 3 as the working electrode was heated to 1.2 A·cm -2 The stability test diagram below.
[0036] Figure 5 TEM images of the dual-phase nanostructured alloy hydrogen evolution catalyst prepared in Example 2. Among them, a is a SEM image at low magnification; b is a SEM image at high magnification; c-c5 are EDS element analysis results under SEM mode; d and e are TEM images at different magnifications.
[0037] Figure 6 yes Figure 5 Magnified view of the inset in d.
[0038] Figure 7 TEM images of the dual-phase nanostructured alloy hydrogen evolution catalyst prepared in Example 1. h is a SEM image at low magnification; i is a SEM image at high magnification; j-j5 are EDS element analysis results under SEM mode; k and l are TEM images at different magnifications.
[0039] Figure 8 yes Figure 7 Magnified view of the inset in k.
[0040] Fig. 9TEM images of the dual-phase nanostructured alloy hydrogen evolution catalyst prepared in Example 3. Among them, a is a SEM image at low magnification; b is a SEM image at high magnification; c is a TEM image at low magnification; d1 and d2 are local enlarged images of the framed portion in c; d3 is a three-dimensional atomic overlap Gaussian function fitting mapping image of the framed portion in c; e to e4 are EDS element analysis images under TEM mode.
[0041] Fig.10 TEM images of the dual-phase nanostructured alloy hydrogen evolution catalyst prepared in Example 3 under HAADF mode. a and b are low-magnification TEM images under HAADF mode; c is a high-magnification TEM image under HAADF mode; and d is an EDS element line scanning analysis image in c.
[0042] Fig.11 yes Fig.10 Magnified view of the inset in b. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0044] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0045] The full English name of electrocatalytic hydrogen evolution reaction is Electrocatalytic Hydrogen Evolution reaction, abbreviated as HER.
[0046] The full name of linear voltammetry is Linear Sweep Voltammetry, abbreviated as LSV.
[0047] The application of Ru-based catalysts is also limited because of the strong interaction between Ru and H atoms. According to the catalyst adsorption kinetics, the strong interaction between Ru and H atoms will hinder the desorption of H2, resulting in a decrease in the productivity of hydrogen. Therefore, it is crucial to rationally adjust the electronic structure of Ru-based catalysts and the desorption energy of H2.
[0048] The heterogeneous phase structure has different electronegativity and work function. The electrons will be transferred in a directional manner at the phase interface to induce charge redistribution, and its electronic structure and charge transport characteristics are optimized, thereby enhancing its catalytic activity. The present invention mainly uses the synergistic effect of the heterogeneous phase structure and the ruthenium-based catalyst to reasonably adjust the electronic structure and H2 desorption energy of the twin-phase nanostructured alloy hydrogen evolution catalyst, so that the prepared twin-phase nanostructured alloy hydrogen evolution catalyst exhibits excellent catalytic performance in electrochemical water decomposition.
[0049] The technical solution of the present invention is further described below through specific embodiments.
[0050] In the following examples, the methods described are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0051] In the following embodiments, the volume percentage of the HNO3 solution is 50 vol.%. The purity of the high-purity argon gas is ≥ 99.9%.
[0052] Example 1
[0053] A method for preparing a dual-phase nanostructured alloy hydrogen evolution catalyst comprises the following steps:
[0054] Step 1, pretreatment of carbon cloth substrate:
[0055] In order to remove grease and impurities on the surface of the carbon cloth substrate, distilled water and anhydrous ethanol were used to clean the surface of the carbon cloth substrate in turn; then it was immersed in 50 vol.% HNO3 solution and kept at 60°C for 2h to improve the hydrophilicity of the carbon cloth substrate; then the immersed carbon cloth substrate was taken out, the acid solution was washed with distilled water, and vacuum dried at 60°C to obtain a pretreated carbon cloth substrate.
[0056] Step 2, preparation of dual-phase nanostructured alloy hydrogen evolution catalyst:
[0057] Ru, Mn, and Nb were used as targets. Before deposition, the distance from the pretreated carbon cloth substrate to the target was adjusted to 15 cm, and the magnetron sputtering system was evacuated to a vacuum degree of 5×10 -5 Pa; before starting deposition, high-purity argon gas is filled into the sputtering chamber to make the working pressure reach 0.2Pa, and the mass flow rate of the sputtering gas argon is set to 50sccm; the substrate temperature is maintained at 25°C.
[0058] Sputtering was started, with the Ru target's sputtering power set to 80 watt; the Nb target's sputtering power set to 50 watt, and the sputtering voltage set to 270 V; and the Mn target's sputtering power set to 80 watt, and the sputtering voltage set to 430 V.
[0059] Under the action of the electric field, the electrons will collide with argon atoms when flying to the substrate, causing the argon gas to be ionized. Under the action of high pressure, the Ar atoms are ionized into Ar + Ions and electrons; Ar + Ions are used as incident ions, bombarding the target under the action of the electric field, so that the neutral atoms or molecules on the surface of the target obtain sufficient kinetic energy to detach from the surface of the target and deposit on the surface of the pretreated carbon cloth substrate to form a thin film. The deposition rate is set to 12.5nm / min, and the deposition time is 60min, so that the crystal-crystal nano dual-phase structure film is deposited on the carbon cloth substrate, and a dual-phase nanostructured alloy hydrogen evolution catalyst is prepared.
[0060] The dual-phase nanostructured alloy hydrogen evolution catalyst prepared in Example 1 is obtained by depositing a dual-phase nanostructured alloy on the surface of a carbon cloth substrate. The dual-phase nanostructured alloy is composed of a Mn-rich phase and a Mn-poor phase, and an O-rich interface is formed between the Mn-rich phase and the Mn-poor phase. The chemical formula of the Mn-rich phase is Ru 50~60 Mn 20~30 Nb 20~22 O 3~8 ; The chemical formula of the Mn-poor phase is Ru 75~60 Mn 10~15 Nb 22~24 ; The size of the Mn-rich phase is 4nm~6nm.
[0061] The dual-phase nanostructured alloy in Example 1 can be used as Ru 56 Mn 30 Nb8O6 bicrystalline hydrogen evolution catalyst for ampere-level hydrogen evolution. Example 1 By controlling the composition of Mn and Ru elements, Mn-rich phases of different sizes are obtained, and the formation of O-rich interface is promoted through the synergistic effect of Mn-rich phase and Mn-poor phase. The O-rich interface enhances the charge transfer and water dissociation kinetics, optimizes the hydrogen adsorption / desorption process, and thus improves the HER performance. In addition, the high-density O-rich interface provides abundant active sites and improves the catalytic performance.
[0062] Example 2
[0063] A method for preparing a dual-phase nanostructured alloy hydrogen evolution catalyst comprises the following steps:
[0064] Step 1, pretreatment of carbon cloth substrate:
[0065] In order to remove grease and impurities on the surface of the carbon cloth substrate, distilled water and anhydrous ethanol were used to clean the surface of the carbon cloth substrate in turn; then it was immersed in 50 vol.% HNO3 solution and kept at 60°C for 2h to improve the hydrophilicity of the carbon cloth substrate; then the immersed carbon cloth substrate was taken out, the acid solution was washed with distilled water, and vacuum dried at 60°C to obtain a pretreated carbon cloth substrate.
[0066] Step 2, preparation of dual-phase nanostructured alloy hydrogen evolution catalyst:
[0067] Ru, Mn, and Nb were used as targets. Before deposition, the distance from the pretreated carbon cloth substrate to the target was adjusted to 15 cm, and the magnetron sputtering system was evacuated to a vacuum degree of 5×10 -5 Pa; before starting deposition, high-purity argon gas is filled into the sputtering chamber to make the working pressure reach 0.3Pa, and the mass flow rate of the sputtering gas argon is set to 40sccm; the substrate temperature is maintained at 25°C.
[0068] Sputtering was started, with the Ru target sputtering power set to 80 watt; the Nb target sputtering power set to 80 watt, and the sputtering voltage set to 280 V; and the Mn target sputtering power set to 50 watt, and the sputtering voltage set to 270 V.
[0069] Under the action of the electric field, the electrons will collide with argon atoms when flying to the substrate, causing the argon gas to be ionized. Under the action of high pressure, the Ar atoms are ionized into Ar + Ions and electrons; Ar + Ions are used as incident ions, bombarding the target under the action of the electric field, so that the neutral atoms or molecules on the surface of the target obtain sufficient kinetic energy to detach from the surface of the target and deposit on the surface of the pretreated carbon cloth substrate to form a thin film. The deposition rate is set to 12.5nm / min, and the deposition time is 60min, so that the crystal-crystal nano dual-phase structure film is deposited on the carbon cloth substrate, and a dual-phase nanostructure alloy hydrogen evolution catalyst is prepared.
[0070] The dual-phase nanostructured alloy hydrogen evolution catalyst prepared in Example 2 is obtained by depositing a dual-phase nanostructured alloy on the surface of a carbon cloth substrate. The dual-phase nanostructured alloy is composed of a Mn-rich phase and a Mn-poor phase, and an O-rich interface is formed between the Mn-rich phase and the Mn-poor phase. The chemical formula of the Mn-rich phase is Ru 50~60 Mn 20~30 Nb 20~22 O 3~8 ; The chemical formula of the Mn-poor phase is Ru 75~60 Mn 10~15 Nb 22~24 ; The size of the Mn-rich phase is 1nm~2nm.
[0071] The dual-phase nanostructured alloy in Example 2 can be used as Ru 60 MnB 30O5 dual-phase hydrogen evolution catalyst for ampere-level hydrogen evolution. Example 2 By controlling the composition of Mn and Ru elements, Mn-rich phases of different sizes are obtained, and the formation of O-rich interface is promoted through the synergistic effect of Mn-rich phase and Mn-poor phase. The O-rich interface enhances the charge transfer and water dissociation kinetics, optimizes the hydrogen adsorption / desorption process, and thus improves the HER performance. In addition, the high-density O-rich interface provides abundant active sites and improves the catalytic performance.
[0072] Example 3
[0073] A method for preparing a dual-phase nanostructured alloy hydrogen evolution catalyst comprises the following steps:
[0074] Step 1, pretreatment of carbon cloth substrate:
[0075] In order to remove grease and impurities on the surface of the carbon cloth substrate, distilled water and anhydrous ethanol were used to clean the surface of the carbon cloth substrate in turn; then it was immersed in 50 vol.% HNO3 solution and kept at 60°C for 2h to improve the hydrophilicity of the carbon cloth substrate; then the immersed carbon cloth substrate was taken out, the acid solution was washed with distilled water, and vacuum dried at 60°C to obtain a pretreated carbon cloth substrate.
[0076] Step 2, preparation of dual-phase nanostructured alloy hydrogen evolution catalyst:
[0077] Ru, Mn, and Nb were used as targets. Before deposition, the distance from the pretreated carbon cloth substrate to the target was adjusted to 15 cm, and the magnetron sputtering system was evacuated to a vacuum degree of 5×10 -5 Pa; before starting deposition, high-purity argon gas is filled into the sputtering chamber to make the working pressure reach 0.4 Pa, and the mass flow rate of the sputtering gas argon is set to 30 sccm; the substrate temperature is maintained at 25°C.
[0078] Sputtering was started, with the Ru target sputtering power set to 80 watt; the Nb target sputtering power set to 80 watt, and the sputtering voltage set to 280 V; and the Mn target sputtering power set to 80 watt, and the sputtering voltage set to 430 V.
[0079] Under the action of the electric field, the electrons will collide with argon atoms when flying to the substrate, causing the argon gas to be ionized. Under the action of high pressure, the Ar atoms are ionized into Ar + Ions and electrons; Ar + Ions bombard the target as incident ions under the action of the electric field, so that the neutral atoms or molecules on the surface of the target obtain sufficient kinetic energy to leave the surface of the target and deposit on the surface of the pretreated carbon cloth substrate to form a thin film. The deposition rate is set to 16nm / min and the deposition time is 45min, so that the crystal-crystal nano dual-phase structure film is deposited on the carbon cloth substrate to prepare a dual-phase nanostructure alloy hydrogen evolution catalyst.
[0080] The dual-phase nanostructured alloy hydrogen evolution catalyst prepared in Example 3 is obtained by depositing a dual-phase nanostructured alloy on the surface of a carbon cloth substrate. The average molecular formula of the dual-phase nanostructured alloy is Ru 62 Mn 12 Nb 21 The dual-phase nanostructured alloy is composed of a Mn-rich phase and a Mn-poor phase, and an O-rich interface is formed between the Mn-rich phase and the Mn-poor phase. The chemical formula of the Mn-rich phase is Ru 50~60 Mn 20~30 Nb 20~22 O 3~8 ; The chemical formula of the Mn-poor phase is Mn-poor phase component Ru 75~60 Mn 10~15 Nb 22~24 ; The size of the Mn-rich phase is 1nm~2nm.
[0081] The dual-phase nanostructured alloy in Example 3 can be used as Ru 62 Mn 12 Nb 21 O5 dual-phase hydrogen evolution catalyst for ampere-level hydrogen evolution. Example 3 By controlling the composition of Mn and Ru elements, Mn-rich phases of different sizes are obtained, and the formation of O-rich interface is promoted through the synergistic effect of Mn-rich phase and Mn-poor phase. The O-rich interface enhances the charge transfer and water dissociation kinetics, optimizes the hydrogen adsorption / desorption process, and thus improves the HER performance. In addition, the high-density O-rich interface provides abundant active sites and improves the catalytic performance.
[0082] For the convenience of description, the twin-phase nanostructured alloy hydrogen evolution catalyst prepared in the above embodiment is referred to as twin-phase hydrogen evolution catalyst for short; specific preparation conditions and product comparison are shown in Table 1 and Table 2.
[0083] Table 1 Comparison of preparation conditions of dual-phase hydrogen evolution catalysts
[0084]
[0085] Table 2 Comparison of products of dual-phase hydrogen evolution catalysts
[0086]
[0087]
[0088] Note: In terms of atomic percentage, the Mn-rich phase is composed of the following elements: Ru 50%-60%, Mn 20%-30%, Nb 20%-22% and O 3%-8%, totaling 100%.
[0089] Preferably, in terms of atomic percentage, the Mn-poor phase is composed of the following elements: Ru 60% to 75%, Mn 10% to 15% and Nb 22% to 24%, totaling 100%.
[0090] Therefore, Ru 50~60 Mn 20~30 Nb 20~22 O 3~8 As the Mn-rich phase, Ru 60~75 Mn 10~15 Nb 22~24 The composition of the dual-phase hydrogen evolution catalyst prepared in the embodiment of the present invention is the average composition of the dual-phase hydrogen evolution catalyst, which is different from the composition of the Mn-rich phase and the composition of the Mn-poor phase; and the ratio of the Mn-rich phase to the Mn-poor phase will affect the total composition of the dual-phase hydrogen evolution catalyst.
[0091] The following relevant tests are conducted on the dual-phase nanostructured alloy hydrogen evolution catalyst prepared in the above examples.
[0092] Test 1: TEM characterization. Transmission electron microscope, the full name of which is Transmission Electron Microscope, or TEM for short.
[0093] The dual-phase nanostructured alloy hydrogen evolution catalyst prepared in Example 1 was characterized by TEM. Figure 7 and Figure 8 shown.
[0094] Figure 7 TEM images of the dual-phase nanostructured alloy hydrogen evolution catalyst prepared in Example 1. h is a SEM image at low magnification; i is a SEM image at high magnification; j-j5 are EDS element analysis results under SEM mode; k and l are TEM images at different magnifications.
[0095] Figure 8 yes Figure 7 Magnified view of the inset in k.
[0096] Figure 7 The element composition analysis in h shows that the ratio of each element in Ru, Nb and Mn of the dual-phase nanostructured alloy hydrogen evolution catalyst prepared in Example 1 is Ru 56%, Nb 8%, Mn 30%, O 6%, and the total is 100%. Figure 7 The k-graph and Figure 8 The size range of the Mn-rich phase is shown, and the average size of the Mn-rich phase is 4.85 nm.
[0097] The dual-phase nanostructured alloy hydrogen evolution catalyst prepared in Example 2 was characterized by TEM. Figure 5 and Figure 6 shown.
[0098] Figure 5 TEM images of the dual-phase nanostructured alloy hydrogen evolution catalyst prepared in Example 2. Among them, a is a SEM image at low magnification; b is a SEM image at high magnification; c-c5 are EDS element analysis results under SEM mode; d and e are TEM images at different magnifications.
[0099] Figure 6 yes Figure 5 Magnified view of the inset in d.
[0100] Figure 5 The element composition analysis in Figure a shows that the ratio of each element in Ru, Nb and Mn of the dual-phase nanostructured alloy hydrogen evolution catalyst prepared in Example 2 is Ru 60%, Nb 30%, Mn 5%, O 5%, totaling 100%. Figure 5 The d graph in Figure 6 The size range of the Mn-rich phase is shown, and the average size of the Mn-rich phase is 1.45 nm.
[0101] From the above analysis, it can be seen that, compared with Example 1, the average size of the Mn-rich phase in Example 2 is smaller than the average size of the Mn-rich phase in Example 1. It can be seen that the number of the Mn-rich phase in Example 2 is relatively low.
[0102] The dual-phase nanostructured alloy hydrogen evolution catalyst prepared in Example 3 was characterized by TEM. Figures 9 to 11 shown.
[0103] Fig. 9 TEM images of the dual-phase nanostructured alloy hydrogen evolution catalyst prepared in Example 3. Among them, a is a SEM image at low magnification; b is a SEM image at high magnification; c is a TEM image at low magnification; d1 and d2 are local enlarged images of the framed portion in c; d3 is a three-dimensional atomic overlap Gaussian function fitting mapping image of the framed portion in c; e to e4 are EDS element analysis images under TEM mode.
[0104] Fig. 9 d1 and d2 show the existence of transient dislocations and distortions caused by lattice mismatch at the interface between the two phases. d3 is a three-dimensional atomic overlapping Gaussian function fitting map, which further illustrates that the black area in the TEM image is a Mn-rich phase.
[0105] Fig.10 TEM images of the dual-phase nanostructured alloy hydrogen evolution catalyst prepared in Example 3 under HAADF mode. Among them, a and b are low-magnification TEM images under HAADF mode; c is a high-magnification TEM image under HAADF mode; d is the EDS element line scanning analysis image in c. HAADF mode, Chinese name is high-angle annular dark field image mode, is a working mode of scanning transmission electron microscope.
[0106] Fig.11 yes Fig.10 Magnified view of the inset in b.
[0107] Depend on Fig.10 Figure d further illustrates that the black phase in the HADDF mode is a Mn-rich phase. At the same time, O is mainly distributed at the interface. Fig.10 Figure b and Fig.11 The size range of the Mn-rich phase is shown, and the average size of the Mn-rich phase is 1.38 nm.
[0108] Depend on Fig. 9 and Fig.10 It can be seen that the surface of the carbon cloth substrate is completely covered by the twin-phase nanostructured alloy hydrogen evolution catalyst. High-power scanning electron microscopy shows that the surface of the film of Example 3 is rough, which leads to a larger specific exposure area. There is a black phase with an average size of 1.38nm in the material, and the black phase is evenly distributed in the matrix. Elemental analysis of the black phase by EDS can determine that the black phase is a Mn-rich phase. We have successfully prepared a new catalyst combining Mn-rich / Mn-poor by magnetron sputtering, and its catalytic activity and stability are greatly improved compared with commercial Pt / C catalysts.
[0109] From the above analysis, it can be seen that the nano-sized Mn-rich phase is dispersed in the Mn-poor phase, providing abundant O-rich interfaces. Compared with Example 1 and Example 2, the number of O-rich interfaces in Example 3 is increased. The small size and large number of Mn-rich phases result in an increase in O-rich interfaces. The high-density O-rich interfaces provide abundant catalytic active sites and improve the HER catalytic performance.
[0110] Test 2: Hydrogen evolution performance test of the dual-crystal phase hydrogen evolution catalyst of Example 1.
[0111] The double-crystal nanostructured alloy hydrogen evolution catalyst prepared in Example 1 was deposited on the surface of the carbon cloth electrode to prepare a modified electrode; the modified electrode was used as a working electrode to promote the occurrence of hydrogen evolution reaction. 56 Mn 30 Hydrogen evolution performance of Nb8O6 dual-phase hydrogen evolution catalyst.
[0112] The test conditions are: in 1M KOH solution, a three-electrode system is used for linear voltammetric scanning test; a graphite rod is used as a counter electrode, a saturated calomel electrode is used as a reference electrode, and a modified electrode prepared by depositing the double-phase nanostructured alloy hydrogen evolution catalyst of Example 1 on the surface of a carbon cloth electrode is used as a working electrode. The scanning rate is 5mV / s, and 100% iR correction is performed.
[0113] Test results such as Figure 1 As shown. Figure 1 It can be seen that the Ru prepared with the deposition distance of +15cm, deposition rate of 12.5nm / min, and deposition time of 60min 56 Mn 30 Nb8O6 dual-phase hydrogen evolution catalyst at a current density of 10 mA·cm -2 The overpotential is 25.3mV.
[0114] Test 3: Hydrogen evolution performance test of the dual-phase hydrogen evolution catalyst of Example 2.
[0115] The modified electrode prepared by depositing the dual-phase nanostructured alloy hydrogen evolution catalyst prepared in Example 2 on the surface of the carbon cloth electrode was used as the working electrode to promote the occurrence of the hydrogen evolution reaction. 60 Mn5 30 Hydrogen evolution performance of O5 biphasic hydrogen evolution catalyst.
[0116] The test conditions are: in 1M KOH solution, a three-electrode system is used for linear voltammetric scanning test; a graphite rod is used as a counter electrode, a saturated calomel electrode is used as a reference electrode, and a modified electrode prepared by depositing the double-phase nanostructured alloy hydrogen evolution catalyst of Example 2 on the surface of a carbon cloth electrode is used as a working electrode. The scanning rate is 5mV / s, and 100% iR correction is performed.
[0117] Test results such as Figure 1 As shown, from Figure 1 It can be seen that the Ru prepared with the parameters of condensation distance of +15cm, deposition rate of 12.5nm / min and deposition time of 60min 60 Mn5 30 O5 biphasic hydrogen evolution catalyst at 10 mA·cm -2 The overpotential is 20.3mV.
[0118] Test 4: Hydrogen evolution performance test of the dual-phase hydrogen evolution catalyst of Example 3.
[0119] The modified electrode prepared by depositing the dual-phase nanostructured alloy hydrogen evolution catalyst prepared in Example 3 on the surface of the carbon cloth electrode was used as the working electrode to promote the occurrence of the hydrogen evolution reaction. 62 Mn 12 Nb 21 Hydrogen evolution performance of O5 biphasic hydrogen evolution catalyst.
[0120] The test conditions are: in 1M KOH solution, a three-electrode system is used for linear voltammetric scanning test; a graphite rod is used as a counter electrode, a saturated calomel electrode is used as a reference electrode, and a modified electrode prepared by depositing the double-phase nanostructured alloy hydrogen evolution catalyst of Example 3 on the surface of a carbon cloth electrode is used as a working electrode. The scanning rate is 5mV / s, and 100% iR correction is performed.
[0121] Test results such as Figure 1 As shown. Figure 1 It can be seen that the Ru prepared with the parameters of condensation distance of +15cm, deposition rate of 16nm / min and deposition time of 45min 62 Mn 12 Nb 21 O5 biphasic hydrogen evolution catalyst at 10 mA·cm -2 The overpotential is 18mV.
[0122] Table 3 Size and hydrogen evolution performance test results of dual-phase nanostructured alloy hydrogen evolution catalyst
[0123] Example Mn-rich phase size / nm <![CDATA[10mA·cm -2 Overpotential / mV]]> <![CDATA[Tafel slope / mV dec -1 > Example 1 4~6 25.3 36.7 Example 2 1~2 20.3 29.4 Example 3 1~2 18 21.6
[0124] Note: Although the size of the Mn-rich phase in Example 2 is similar to that in Example 3, due to the lower Mn content in Example 2, the amount of the Mn-rich phase formed is less than that in Example 3, so the performance is lower than that in Example 3.
[0125] Tafel slope, also known as Tafel slope in English, is the slope of the straight line segment on the semi-logarithmic curve obtained when the logarithmic value of potential-current density is plotted. Tafel slope can be used to reflect the rate-controlling step of the electrocatalytic hydrogen and oxygen evolution reaction. The size of the slope reflects the catalytic performance of the catalyst. The smaller the value, the better the catalytic performance.
[0126] like Figure 2 As shown, the Ru of Example 3 62 Mn 12 Nb 21 The Tafel slope of the O5 dual-phase hydrogen evolution catalyst is the lowest, which is 21.6 mVdec -1 ; Ru of Example 2 60 MnB 30 The Tafel slopes of the O5 biphasic hydrogen evolution catalyst are 29.4 mV dec -1 ; Ru of Example 1 56 Mn 30 The Tafel slope of the Nb8O6 biphasic hydrogen evolution catalyst is 36.7 mV dec -1 , indicating good electrocatalytic performance.
[0127] Electrochemical impedance spectroscopy, or EIS for short, is one of the important parameters for measuring the performance of electrocatalytic hydrogen evolution. Z' represents the real part of impedance, which is parallel to the x-axis and reflects the resistive response of the electrochemical system to the AC signal; -Z" represents the opposite of the imaginary part of impedance, which is parallel to the y-axis and is related to the capacitance or inductance effect, and is used to describe the non-resistive response in the electrochemical system. In the electrochemical impedance test, by analyzing the changes in Z' and -Z", we can gain a deep understanding of the kinetic process and interfacial reaction characteristics of the electrochemical system.
[0128] Figure 3 The electrochemical impedance spectra of the three-electrode system assembled with the dual-phase nanostructured alloy hydrogen evolution catalysts of Examples 1 to 3 as working electrodes are shown in FIG. 1 , wherein Z′ represents the real part of the impedance; and −Z″ represents the inverse of the imaginary part of the impedance. Figure 3 The inset is an equivalent circuit diagram drawn based on EIS data. s is the solution resistance, R ct is the charge transfer resistor, and CPF 1 is a constant phase angle element. Figure 3 It is fitted according to this equivalent circuit diagram.
[0129] like Figure 3 As shown, the Ru of Example 3 62 Mn 12 Nb 21 The O5 biphasic hydrogen evolution catalyst shows lower charge transfer resistance than the other two biphasic hydrogen evolution catalysts, and R ct =1.96Ω, which shows that the Ru of Example 3 62 Mn 12 Nb 21 The O5 biphasic hydrogen evolution catalyst has stronger charge transfer ability.
[0130] Test 5: Long-term stability test. Long-term stability is another key indicator for evaluating the electrochemical performance of electrocatalysts, especially in industrial applications.
[0131] Figure 4 The three-electrode system assembled with the dual-phase nanostructured alloy hydrogen evolution catalyst of Example 3 as the working electrode was heated to 1.2 A·cm -2 The stability test diagram below.
[0132] like Figure 4 As shown, the Ru of Example 3 62 Mn 12 Nb 21 O5 dual-phase hydrogen evolution catalyst can be used at 1.2A·cm -2It can run stably for 300h at the same current density, and has great industrial application prospects.
[0133] In summary, in the dual-phase hydrogen evolution catalyst of the above embodiment, by controlling the composition of Mn and Ru elements, Mn-rich phases of different sizes are obtained, and the formation of O-rich interface is promoted through the synergistic effect of Mn-rich / Mn-poor dual phases. The O-rich interface enhances the charge transfer and water dissociation kinetics, optimizes the hydrogen adsorption / desorption process, and thus improves the HER performance. In addition, the high-density O-rich interface provides abundant active sites and improves the catalytic performance.
[0134] The experimental results in Tables 2 and 3 show that the content of Mn element can affect the size of the Mn-rich phase, and thus affect the formation size of the highly active O-rich interface.
[0135] Density Functional Theory is short for DFT. DFT calculations have shown that the adsorption energy of *OH on the Ru site adjacent to Nb is significantly greater than that on other Ru sites, indicating that Nb improves the *OH adsorption efficiency of Ru. In the first step of HER, *OH and H2O undergo proton transfer to form *H2O, and high *OH adsorption efficiency can promote the reaction in the first step.
[0136] Ru can significantly affect the catalytic activity. Too high Ru content will reduce the amount of Mn-rich phase, thereby reducing the amount of active interface formed. As an active element, Ru itself also plays an important role in improving the activity of the catalyst. Too low Ru content will reduce the number of catalytic sites, thereby reducing the catalytic activity. Therefore, the Ru content should be controlled at 55% to 65%.
[0137] Through DFT calculation, it is found that in the O-rich interface, O atoms can reduce the energy barrier of active hydrogen conversion to H2. At the same time, O atoms can also improve the efficiency of the H2O dissociation step, resulting in RuMnNbO being superior to Pt-based catalysts in electrochemical H2 release. The O content will affect the formation of the O-rich interface. Too low an O content will lead to insufficient formation of the O-rich interface and reduce the active sites. However, too high an O content will cause excessive oxidation of the metal elements, excessively reducing the adsorption energy of H at the active sites, which is not conducive to catalytic activity. Therefore, the O content should be controlled between 3% and 10%.
[0138] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A dual-phase nanostructured alloy hydrogen evolution catalyst, characterized in that: It includes a substrate and a dual-phase nanostructured alloy deposited on the surface of the substrate; The dual-phase nanostructured alloy is composed of the following elements in terms of atomic percentage: Ru 56% to 62%, Mn 5% to 30%, Nb 8% to 30% and O 5% to 6%, totaling 100%; The dual-phase nanostructured alloy includes a Mn-rich phase and a Mn-poor phase, and an O-rich interface is formed between the Mn-rich phase and the Mn-poor phase, wherein the O-rich interface is a catalytic active site; and the size of the Mn-rich phase is 1 nm to 6 nm.
2. The dual-phase nanostructured alloy hydrogen evolution catalyst according to claim 1, characterized in that: The size of the Mn-rich phase is 1 nm to 2 nm.
3. The dual-phase nanostructured alloy hydrogen evolution catalyst according to claim 1, characterized in that: The atomic percentage of the Mn element in the Mn-rich phase is 20% to 30%; the atomic percentage of the Mn element in the Mn-poor phase is 10% to 15%.
4. The dual-phase nanostructured alloy hydrogen evolution catalyst according to claim 3, characterized in that: In terms of atomic percentage, the Mn-rich phase is composed of the following elements: Ru 50% to 60%, Mn 20% to 30%, Nb 20% to 22% and O 3% to 8%, totaling 100%.
5. The dual-phase nanostructured alloy hydrogen evolution catalyst according to claim 3, characterized in that: In terms of atomic percentage, the Mn-poor phase is composed of the following elements: Ru 60% to 75%, Mn 10% to 15% and Nb 22% to 24%, totaling 100%.
6. A method for preparing the dual-phase nanostructured alloy hydrogen evolution catalyst according to any one of claims 1 to 5, characterized in that: The following steps are involved: The invention adopts magnetron sputtering technology and controls the contents of Mn and Ru elements to deposit a dual-phase nanostructured alloy containing a Mn-rich phase and a Mn-poor phase on the surface of a substrate, and forms an O-rich interface between the Mn-rich phase and the Mn-poor phase of the dual-phase nanostructured alloy; and adjusts the size of the Mn-rich phase to adjust the size and number of the O-rich interface, so as to provide catalytic active sites.
7. The method for preparing the dual-phase nanostructured alloy hydrogen evolution catalyst according to claim 6, characterized in that: The process parameters for depositing the dual-phase nanostructured alloy are: Ru, Mn, and Nb are used as targets; The background vacuum is 1×10 -5 Pa~5×10 -5 Pa, the working gas pressure is 0.2Pa~0.4Pa, the distance between the substrate and the target is 15cm; the sputtering temperature is 20℃~30℃; Using Ru as the target, the sputtering power is 50 watt to 80 watt; Using Mn as the target, the sputtering power is 50 watt to 80 watt, and the sputtering voltage is 270 V to 430 V; Using Nb as the target, the sputtering power is 50 watt to 80 watt, and the sputtering voltage is 175 V to 280 V; The deposition time is 45 to 60 minutes.
8. Use of the dual-phase nanostructured alloy hydrogen evolution catalyst according to any one of claims 1 to 5 in electrocatalytic hydrogen evolution.
9. Use of the dual-phase nanostructured alloy hydrogen evolution catalyst according to claim 8 in electrocatalytic hydrogen evolution, characterized in that: The specific application method includes the following steps: The modified electrode is prepared by depositing a dual-phase nanostructured alloy dual-phase hydrogen evolution catalyst on the surface of a carbon cloth electrode; The modified electrode was used as the working electrode, the graphite rod was used as the counter electrode, and the saturated calomel electrode was used as the reference electrode to form a three-electrode system for electrocatalytic hydrogen evolution.
Citation Information
Patent Citations
Nitride catalyst and forming method thereof
CN111250129A
AB2 type intermetallic compound for hydrolysis catalyst as well as synthesis method and application of AB2 type intermetallic compound
CN112626551A
Alpha-MnO2 nanorod loaded RuO2 lithium-sulfur battery positive electrode catalyst and preparation method thereof
CN117548105A
Hydrogen evolution and oxygen evolution bifunctional catalyst as well as preparation method and application thereof
CN119016064A
Multiphase hydrogen-permeable alloys and hydrogen-permeable alloy membranes
JP3749953B1